Mikołaj Krzysztof “The Orphan” Radziwiłł’s and Albrycht Władysław Radziwiłł’s Seven Documents and Letters from the End of 16th and the Beginning of 17th Centuries Concerning Tithes and Other Benefits for the Catholic Parish Church in Čarnaŭčycy - Gołaszewski, Łukasz (Vilnius University Open Series, 2024)
The present paper contains an editing of seven documents and letters concerning the tithes from Radziwiłł’s estates near Brest for the Catholic parish church in Čarnaŭčycy and St. Barbara provostry in Brest. Senders were two members of the Radziwiłł family: Mikołaj Krzysztof “The Orphan” and Albrycht Władysław and addresses parish priests and land-stewards. This documents are interesting sources of knowledge about relations between them and landlord’s activity in the field of solutions to the disputes about tithes.
Keywords: tithes in the Grand Duchy of Lithuania; Catholic Church in Brest; Catholic Church in Čarnaŭčycy; Mikołaj Krzysztof “The Orphan” Radziwiłł; Albrycht Władysław Radziwiłł; relations between magnates and Catholic clergy in Polish-Lithuanian Commonwealth